Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1590/0004-282x20150032
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein A53T mutation is not frequent on a sample of Brazilian Parkinson’s disease patients

Abstract: Parkinson's disease (PD) is one of the major degenerative disorders, affecting 2% of the population over 65 years and up to 4% in people over 85 years 1 . In Brazil, statistics show that the incidence of PD amounts to 150/200 cases per 100,000 inhabitants 2 . Most cases of PD are idiopathic 3 . However, in approximately 5%-10% of the cases, there is a genetic component with both dominant and recessive inheritance patterns 3 . The chromosomal loci linked to the familial forms of PD are termed PARK1-13. These lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This review assessed 3014 studies, of which 73 met the inclusion criteria 20,35–106 . The process detailing the step‐by‐step inclusion and exclusion criteria is summarized in the PRISMA flow diagram 107 shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…This review assessed 3014 studies, of which 73 met the inclusion criteria 20,35–106 . The process detailing the step‐by‐step inclusion and exclusion criteria is summarized in the PRISMA flow diagram 107 shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last 15 years, the numerous studies have confirmed that genetic factors contributed to the complex pathogenesis of PD. Some studies found that some vital point of some genes could induce the familial PD, which included the SNCA, Parkin, DJ-1, PINK 1, LRRK2, VPS35, LRRK2, and GBA [3][4][5][6][7]. But some other studies showed that the environmental exposure history with the paraquat, rotenone, manganese, and organochlorines was linked with PD [8].…”
Section: Introductionmentioning
confidence: 99%